PENGECUALIAN RAHASIA BANK BAGI KURATOR SEBAGAI BENTUK KESEIMBANGAN ANTARA KEPENTINGAN PRIBADI NASABAH DAN KEPENTINGAN UMUM - Wulandari, Mona (The Juris, 2025)
The principle of bank secrecy regulation is basically not absolute, but relative, which means that the confidentiality of customers remains protected, but if there are certain things the principle of bank secrecy can be set aside. This condition can be an obstacle for the Curator in carrying out his duties because the existence of bank secrecy provisions causes the Curator to be unable to identify and secure the debtor’s bank account because in the banking law before the enactment of the Law on Development and Strengthening of the Financial Sector (P2SK) did not regulate it clearly, firmly and state expressis verbis (clear and firm meaning). The type of research used in this writing is normative legal research. The exception to the opening of Bank Secrecy for curators through a Commercial Court decision is an exception that is regulated for the public interest, especially in the bankruptcy process. This aims to allow the curator to access the financial information of debtors who are in bankruptcy for the sake of settling bankrupt assets. This exception balances the privacy rights of bank customers and the public interest in law enforcement. The exception to bank secrecy for curators is an example of the balance between the personal interests of customers (privacy) and the public interest (in this case, the fulfillment of debtor obligations and the protection of creditor rights). This exception is strictly regulated to prevent abuse and ensure that financial information is only accessed by authorized parties in a legitimate bankruptcy process.